login
A358663
Decimal expansion of the solution to (1 - (x + 1)^(x^2 - 1))/x = (1 - (x - 1)^(x + 1))/(x - 2).
3
1, 5, 4, 7, 2, 2, 7, 1, 9, 3, 8, 0, 9, 3, 7, 2, 7, 5, 0, 2, 0, 1, 8, 2, 2, 6, 2, 4, 1, 2, 6, 5, 3, 5, 4, 6, 4, 8, 0, 2, 9, 5, 8, 5, 6, 2, 8, 2, 3, 9, 3, 5, 6, 3, 4, 3, 5, 8, 2, 0, 2, 9, 4, 7, 4, 7, 1, 0, 1, 9, 8, 6, 2, 8, 1, 4, 5, 8, 9, 5, 1, 2, 2, 0, 8, 1, 8, 2, 9, 6
OFFSET
1,2
FORMULA
Decimal expansion of the solution to (1 - a^(ab))/(1 - a) = (1 - b^a)/(1 - b), where a = x + 1 and b = x - 1.
EXAMPLE
x = 1.547227193809372750201822...
MATHEMATICA
RealDigits[x /. FindRoot[(1 - (x + 1)^((x - 1) (x + 1)))/x == (1 - (x - 1)^(x + 1))/(x - 2), {x, 1.5}, WorkingPrecision -> 100]][[1]]
CROSSREFS
KEYWORD
nonn,cons
AUTHOR
Wesley Ivan Hurt, Nov 25 2022
STATUS
approved